An experimental manipulation of social uncertainty to explore the relation between vulnerable narcissism and proactive aggression. (July 2023) - Kim, Hyunah; Barry, Christopher T.; Fowler, Ashley N.; Halter, Brianna M.; Radcliffe, Samantha L.
Abstract: This study developed an experimental manipulation for social uncertainty and used an analogue aggression task to examine the moderating role of uncertainty in the relation between narcissism and aggression. The sample consisted of 186 college students who experienced either an uncertain or certain social situation where they had a conversation with another participant and then assigned tangram puzzles to their conversation partner task, as an indicator of aggression. The experimental manipulation of social uncertainty worked such that participants in the uncertain condition experienced higher distress and uncertainty than those in the certain condition. However, this distress did not translate to aggression. This study proposes a potential experimental method to induce distress from uncertainty and also suggests what should be considered when designing experimental methods to investigate proactive aggression in the context of ambiguous social situations. Highlights: Tested an experimental manipulation of uncertainty in relation to aggression Uncertainty hypothesized to moderate narcissism-proactive aggression relation The uncertainty condition related to higher distress and uncertainty than the certain condition However, experimental uncertainty was not related to higher aggression.